Male Infertility and Risk of Nonmalignant Chronic Diseases: A Systematic Review of the Epidemiological Evidence - Glazer, Clara Helene; Bonde, Jens Peter; Eisenberg, Michael L.; Giwercman, Aleksander; Hærvig, Katia Keglberg; Rimborg, Susie; Vassard, Ditte; Pinborg, Anja; Schmidt, Lone; Bräuner, Elvira Vaclavik (Seminars in Reproductive Medicine, 2017)
The association between male infertility and increased risk of certain cancers is well studied. Less is known about the long-term risk of nonmalignant diseases in men with decreased fertility. A systemic literature review was performed on the epidemiologic evidence of male infertility as a precursor for increased risk of diabetes, cardiovascular diseases, and all-cause mortality. PubMed and Embase were searched from January 1, 1980, to September 1, 2016, to identify epidemiological studies reporting associations between male infertility and the outcomes of interest. Animal studies, case reports, reviews, studies not providing an accurate reference group, and studies including infertility due to vasectomy or malignancy were excluded. The literature search resulted in 2,485 references among which we identified seven articles fulfilling the eligibility criteria. Of these, four articles were prospective (three on risk of mortality, one on risk of chronic diseases) and three were cross-sectional relating male infertility to the Charlson Comorbidity Index. The current epidemiological evidence is compatible with an association between male infertility and risk of chronic disease and mortality, but the small number of prospective studies and insufficient adjustment of confounders preclude strong statements about male infertility as precursor of these outcomes.
Keywords: male infertility; comorbidity; mortality; chronic diseases